التفكير الاختراقي لدى مدرسي المرحلة الإعدادية في محافظة واسط - Farhan Awad, Ali; مجيد حميد عبد الله (Journal of College of Education, 2022)
Abstract of the research The current research aimed to identify: The degree of breakthrough thinking among middle school teachers in Wasit governorate and the differences of statistical significance according to the variables (gender and specialization). The current research sample was selected by the stratified random method of proportional distribution, reaching (400) teachers and schools from Wasit Governorate. In order to achieve the objectives of the research, the researcher adopted the Hanoun scale (2018) to measure penetrating thinking translated into the Arabic language, and the scale consisted of (36) paragraphs distributed into four domains, as the researcher calculated the psychometric properties of the scale, according to the validity in two ways (apparent honesty and construct validity), as was verified. There are two methods of stability (the re-test method, and the Fakronbach method). Then the researcher reached the following results: • Middle school teachers have breakthrough thinking. • There are no statistically significant differences in breakthrough thinking according to the gender and specialization variable. • There are no statistically significant differences according to the interaction between sex and specialization.